(Po)wolna edukacja religijna - Dąbrowski, Szymon (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The text is an attempt to show how the premise of slow education and broader slow life can become a real alternative to the current state of religious education in Polish schools. This is the search for a way out of today’s crisis in which religious school education has fallen as well as the need and potential of religious education to address the challenges of global society. It is also about promoting overt but critically cultivated axiological education, which in the paradigm of neoliberal education has been marginalized or eliminated, it’s necessity not only in the field of pedagogical research, but also in the space of broadly understood social sciences.
Keywords: critical religious education; educational alternative; religious education; slow education; slow life